Analysis of prohibited drugs and proteins by mass spectrometry - Kwon, Oh-Seung (한국분석과학회, 2020)
(2020한국분석과학회 지올분석과학상 수상강연) Analysis of prohibited drugs and proteins by mass spectrometry Oh-Seung Kwon; Doping Control Cener, KIST; Corresponding author: oskwon@kist.re.kr Many different kinds of prohibited doping drugs such as low-molecular weights or macromolecules (proteins) are annually increasing in the WADA list. The analytical methods require multiplexing and simultaneous high-throughput strategy for the purpose of not only accurate reporting of the result on time but also saving the sample volume for further confirmation. Due to recent advances of mass spectrometry technology with highly improved sensitivity and selectivity, these instruments are a main tool in the areas of doping drug analysis and biomarker screening for therapeutic diagnosis. In 1980-1990s when LC/MS was not popularly available, a GC/MSD was main instrument for doping drug analysis after enzyme hydrolysis, liquid extraction and derivatization. Recently, however, liquid chromatography/quantum mass spectrometry are popularly used. First, in order to improve the analytical methods for screening hundreds of the prohibited drugs, the optimal WCX-SPE procedure including washing and elution conditions with different pH solutions was investigated for method validation by using 2 ml urine. The cartridge were eluted consecutively with acidic and basic solutions with 2 ml each, the eluate were dried and reconstituted with a diluted sample matrix (20% urine sample in 200 μl solution). Second, doping drugs of large peptides, growth hormone releasing peptides were determined in urine by LC/MS-MS, and insulin-like growth factor-1 (IGF-1), insulin and their biosimilars were analyzed in serum by nano LC-MS/MS. Third, relative quantification of protein was conducted in different brain regions of mice EAE models by nano LC/MS-MS using 6-plex tandem mass tags (TMT). The homogenate of tissues was treated by con
Keywords: Prohibited drugs; null; Doping; null; Proteomics; null; Mass spectrometry; null; TMT